2017
DOI: 10.1111/scs.12545
|View full text |Cite
|
Sign up to set email alerts
|

Visibility and meanings of partnership in health care for older people who need support to live at home

Abstract: We concluded that older people who need support to live at home are not highly visible to health providers, policymakers and researchers as a central partner and consumer to be meaningfully engaged in shaping their health care. Opportunities to address persistent issues with quality of health care may in future be achieved through stronger partnerships between older people and health providers, to find new ways to improve the quality of care for older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(30 citation statements)
references
References 40 publications
(64 reference statements)
0
29
0
1
Order By: Relevance
“…The main results showed that older people in community home care experienced the RNs leading close to them as their ‘own RNs’, or in their words, ‘my RN’ (Figure 1), and included working in partnership with the RN. In a related study, Gregory et al, (2018) showed that older people wanted to work in partnership in their healthcare decisions and desired to contribute with an impact on their own health care. This study showed that older people were capable of working in partnership with the RN and that the caring relationship was based on trust and confidence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main results showed that older people in community home care experienced the RNs leading close to them as their ‘own RNs’, or in their words, ‘my RN’ (Figure 1), and included working in partnership with the RN. In a related study, Gregory et al, (2018) showed that older people wanted to work in partnership in their healthcare decisions and desired to contribute with an impact on their own health care. This study showed that older people were capable of working in partnership with the RN and that the caring relationship was based on trust and confidence.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, they must let unknown people into their homes, including those that they did not choose themselves (Jonasson et al, 2019). Older people are often seen as a recipient and not as a partner in care (Gregory et al, 2018), although they do want to be involved in decisions about their own care at home (Gregory et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, FGI participants emphasised that professional caregiving is essential to ensure the safety of the older adults residing in nursing homes and provide quality care as well as to build partnership with families (Jang, 2020 ). As relevant studies have reported that staff competence and practice of nursing activities are related to coherent caregiving and establishment of role boundaries (Gregory et al, 2018 ; Mikkelsen & Frederiksen, 2011 ), professional care is crucial in the formation of partnership. From a nursing management perspective, the formation of an effective partnership between staff and families is associated with enhanced job satisfaction among the staff, enhanced satisfaction with the facility among families, reduced role conflicts among the staff, and ultimately, with elevated quality of life among the older adult residents (Puurveen et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since the World Health Organization declared promoting the health of everyone in 1978 as a major goal (World Health Organization, 1978 ), the concept of partnership has been used as a collaborative relationship between healthcare professionals and clients with a greater focus on the patient's health status and enhancement of health management skills (Gregory et al, 2018 ). In nursing studies, partnership‐related research has been conducted in various aspects, including for meaning and concept analysis of partnerships (Lee, 2007 ), the development of a partnership model (Coyne & Cowley, 2007 ; Wiggins, 2008 ), and the application of parent and family participation programs such as interventions for family involvement care (Mackie et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kysyttäessä kokemuksia kotihoidosta haastateltavat toivat esille, että heidän vahvuuksiaan, yksilöllisiä tarpeitaan ja persoonallisuuttaan ei ole riittävästi hyödynnetty ja mahdollistettu kotihoidossa. Tämä on tuotu esille myös aikaisemmissa tutkimuksissa (Gregory, Mackintosh, Kumar & Grech 2018;Róin 2017;Tiilikainen, Hujala, Kannasoja, Rissanen & Närhi 2019;Turjamaa ym. 2015; Vernooij-Dassen &Moniz-Cook 2016.)…”
Section: Tutkimustulosten Tarkasteluunclassified